Captain underpants and the revolting revenge of the radioactive robo-boxers ebook - Pilkey, Dav (Captain Underpants, 2020)
George and Harold have to figure out how to fix history in the tenth book in this #1 New York Times bestselling series by Dav Pilkey, the author and illustrator of Dog Man! George and Harold have been turned into evil zombie nerds doomed to roam a devastated, postapocalyptic planet for all eternity! Unfortunately, the boys can't count on Captain Underpants for help because Tippy Tinkletrousers and his time-traveling hijinks prevented George and Harold from creating him in the first place! With Tippy having changed the course of human history forever, George and Harold will have to figure out a way to change it back!